Afectaciones del trabajo infantil en el desarrollo sociocultural de niños y niñas que trabajan en el centro de Machala - Valarezo Rambay, Einer Rigoberto (My University, 2020)
The research Affectations of child labor in the sociocultural development of children working in the center of Machala, analyzes the types of work they do, age, hours, days, whether they study or not, disability, since frequently it will be observed in the streets of the city the increase of children in work activities, associated family businesses or acting as employees. Situation that leads to raising the question What are the etiological factors that affect the participation of children in work activities not according to their chronological - evolutionary age and the repercussions on their sociocultural development The objective: to identify the impact generated by child labor on integral development, through the analysis of quantitative variables, aimed at promoting dissemination actions and design of compensatory social policies that contribute to improving the living conditions of children and girls of school age. Methodologically, the census survey technique has been applied estimating units of information located in the context of the study. The most outstanding results show that 50% of working children do not study, the age of 11 and 14, most common activities: sales of vegetables and candies. To minimize the morphological, physiological and emotional consequences, there is a need to create and promote social policies that have as protagonists the institutional instances of the state such as GADs, provincial, cantonal and parochial together with the ministerial representations established in the province El Oro.
La investigación Afectaciones del trabajo infantil en el desarrollo sociocultural de niños y niñas que trabajan en el centro de Machala, analiza los tipos de trabajo que realizan, la edad, las horas, jornadas, si estudian o no, discapacidad, ya que frecuentemente se observar en las calles de la ciudad el incremento de niños en actividades laborales, asociados negocios familiares o actuando como empleados. Situación que lleva a plantear la interrogante. Cuáles son los factores etiológicos que inciden en la participación de los niños y niñas en actividades laborales no acordes a su edad cronológica - evolutiva y las repercusiones en su desarrollo sociocultural El objetivo: identificar el impacto generado por el trabajo infantil en el desarrollo integral, a través del análisis de variables cuantitativas, orientado a promover acciones de difusión y diseño de políticas sociales compensatorias que tribute a mejorar las condiciones de vida de los niños y niñas en edad escolar. Metodológicamente se ha aplicado la técnica de la encuesta censal estimando unidades de información ubicadas en el contexto de estudio. Los resultados más sobresalientes muestran que el 50% de niños que trabajan no estudian, la edad de 11 y 14 años, actividades más usuales: ventas de verduras y caramelos. Para minimizar las consecuencias en lo morfológico, fisiológico y en emocional se plantea la necesidad de crear e impulsar políticas sociales que tengan como protagonistas a las instancias institucionales del estado como GADs, provincial, cantonal y parroquial junto a las representaciones ministeriales asentadas en la provincia de El Oro.
Keywords: AFECTACION; SOCIOCULTURAL; NIÑO; POBREZA